Applying learning factory in lean management: The experience of undergraduate students in a Malaysian public university - Mohd Ghazali, Maarof (Faculty of Management & Muamalah, KUIS, 2020)
Employee’s competency plays an important role in the organization sustainability. This is important as the business environment is facing globalization effect and changing customer’s demand. However, there is a mismatched between workforce qualification and the changes in the business world. Therefore, universities play a big role in preparing students for the job market. The Faculty of Industrial Management, Universiti Malaysia Pahang has setup a learning factory in 2016 and embed it into the curriculum from October 2017 onwards. This research employed qualitative research in its data collection analysis. The experience of 56, second year undergraduate students who have used the learning factory in the Lean Management were reported. The result from this research reveal that learning factory help students to be exposed to real-life industry, improve student's understanding, gain practical experience, ability to relate theory with practical experience, learn new knowledge, make learning experience more interesting, and help to adapt to industrial life (Leave one space here).